Trade Integration and Global Value Chains in Sub-Saharan Africa : In Pursuit of the Missing Link - Allard, Celine (Departmental Papers; Departmental Paper ;, 2016)
This analysis of the extent of trade integration of sub-Saharan African (SSA) countries in the global economy as well as within the region over the 1995-2013 period focuses on four key concepts: (1) trade openness, captured by import and export flows; (2) the centrality in the global and regional trade network, a measure that takes into account not only the size of trade but also the number of trade partners and the respective weight of these trade partners in global trade; (3) gravity model estimates that account for country- and region-specific determinants of bilateral trade flows; and (4) global value chain (GVC) integration. Using both existing data and a newly available dataset based on multiregion input and output tables, this analysis led to several findings: (1) trade openness has increased strongly; (2) integration in the global economy has made the region more vulnerable to external shocks; (3) levels of trade flows emanating from sub-Saharan Africa are still only half the magnitude of those experienced elsewhere in the world; (4) the region still has ways to go to better integrate in GVCs; and (5) it is more critical than ever to make progress in filling the infrastructure gap by lowering tariff and nontariff barriers, improving the business climate and access to credit, and continuing to enhance education outcomes.